Pengaruh Think Pair Share Terhadap Kemampuan Mengembangkan Teks Hikayat ke dalam Bentuk Cerpen Siswa Kelas X SMA Negeri Batusangkar - Hasibuan, Siti Apsona; Afnita, Afnita; Mamat, Simah (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2023)
The purpose of the study was to determine the effect of Think Pair Share on the ability to develop hikayat text into short stories of class X SMA Negeri 2 Batusangkar students. Quantitative research is a type of research conducted using experimental methods. One Group Pretest-Posttest design is an experimental design used in this study. The data of this research is the result of the final test of converting short story text. Through pre-test and post-test, data was collected that showed students' ability to develop hikayat text into short stories. The t-test result was 10.731> 1. 68, meaning that H0 was rejected and H1 was accepted. So, it can be concluded that there is an average difference between the results of the pretest and posttest, which means that there is an effect of Think Pair Share to develop the skills of hikayat text into short story text of class X SMA Negeri 2 Batusangkar students.